"There Is a Lot of Community Spirit Going On." Middle Managers' Stories of Innovation in Home Care Services. (May 2019) - Sørly, Rita; Krane, Martin Sollund; Bye, Geir; Ellingsen, May-Britt
Background : There is a need for qualitative studies on imposed innovation in home care services in welfare societies. The municipalities are key actors in the field of innovation in the public sector. As innovations often are interpreted to be in conflict with values in health care, we need knowledge on how policy changes and imposed innovations are understood and handled by middle managers working in the sector.Aim: We aim to explore how middle managers react to imposed innovation in health services through their storytelling. The research question was "What can middle managers' stories of imposed innovation tell us about their role in, and some important prerequisites for, innovation processes in municipal health-care services?"Methods: A narrative study of experiences with municipal innovation among middle managers in Norway. In this article, we do a thematic analysis of interviews with seven female middle managers who work in a home care service department.Findings: The study develops an understanding of which frameworks are required within a home care service to meet constant demands for innovation. Innovations are understood by the managers as results of policy changes and new public management demands and as a troublesome burden. We find the prerequisites for implementing innovations to be (1) trust-based management, (2) flexibility and dynamics, (3) continuity of care, and (4) emphasis on competence . These prerequisites are further interpreted in relation to dominant discourses on innovation at the macro, meso, and micro levels within the storytelling contexts.Conclusion: Imposed innovations require a negotiating practice in cross-disciplinary environments at all levels in the organization.